REVEALING EFL STUDENTS’ GRAMMATICAL ERROR IN CAUSE-EFFECT ESSAY - Lestari Setyowati; Sony Sukmawan; Ana Ahsana El-Sulukiyyah; Nur Indah Ramadhani (Jurnal Bahasa Lingua Scientia, 2020)
The purpose of this study is to investigate 1) the types of the error made by the fourth-semester students of PGRI Wiranegara University in writing a cause-effect essay, and 2) the most frequent error made by the students in making cause-effect essay. The research uses descriptive quantitative design. The subjects of the study were the fourth-semester students of the English Education Study Program in the academic year 2019/2020 in the Faculty of Pedagogy and Psychology, University of PGRI Wiranegara, East Java, Indonesia. The instrument used in the study was mainly a documentation of the students’ composition. The researchers used Hewing's theory in 2002 to analyze the errors. The data was analyzed based on seven categories. They are: (1) Errors in using verb group, (2) Errors in the agreement between subject and verb, (3) Errors in the use of the article, (4) Errors in the use preposition, (5) Errors in pluralization, (6) Error in the use of pronoun and (7) Error in the use of a conjunction. The result of the study shows that In total, there were 406 errors made by the students in writing cause-effect essay.The most frequent error made by the students is the use of preposition. This error occur 149 times in the students’ essay (36.70%). The second most frequent error is the use of article (28.57%) which occurs 116 times in the students’ essay. And the third most frequent error is in the use of subject-verb agrrement (7.88%) and pluralization (7.88%).